Pollution pattern of volatile organic compounds (VOCs) in drinking water using chemometrics data analysis methods - Soh, Shiau Chian; Abdullah, Md. Pauzi (Penerbit Universiti Sains Malaysia, 2004)
The occurrence of volatile organic compounds (VOCs) in drinking water create a major concern over the possible health risk because, even at very low concentrations, many of these materials are toxic,carcinogenic or mutagens (Sacks & Akard,1994). As considerable quantities of VOCs are manufactured in Malaysia, their use is certainly ubiquitous. VOCs are contained in many manufactured products, including paints, adhesives, gasoline, and plastics (Nikolaou et al., 2002).